(untitled) (Experimental biology, 2015)
The results of the study at specialized feeding forages and effects of immunomodulator observed multidirectional their effect on the body’s resistance fish.It is found that the positive effect of immunomodulators as fish breeding and biological indicators, and on the status of fish immunofiziologichesky.